EDUKASI DAN PRAKTEK MENGGOSOK GIGI PADA ANAK TK DAN MENCUCI TANGAN PADA SISWA/I SEKOLAH DASAR DI DESA SUMBER WULUH JAWA TIMUR - Aji Humaedi; Frida Octavia Purnomo; Desi Dwi Murti Br Tarigan; Erika Sinta Wati (Journal of Social Comunity Services, 2024)
Health is a state of health, whether physically, mentally, spiritually or socially that allows everyone to live a productive life socially and economically. Health that needs to be considered, especially in children, is oral and dental health, as well as hand hygiene. The purpose of this service is to provide understanding to local children about the importance of maintaining health and hygiene. Community service is carried out through educational activities through poster media and practice accompanied by singing. The method carried out in this service is in the form of filling out questionnaires. The results of this service provide an overview of the increase in enthusiasm and increase children's understanding of how to wash hands and brush teeth properly and correctly, so as to obtain data carried out with normality and homogeneity tests, then proceed with paired sample t tests using SPPS. Then the results of data analysis were obtained in the form of significance values stating that H0 was rejected and Ha was accepted, which means that there was an influence in providing treatment before (pre test) and after (post test) education and practice of washing hands.